João Barbosa Rodrigues: o caráter de visualidade da ilustração Botânica no Brasil - Julianele, Regina Lemgruber (1997)
Analyses botanical illustration in Brazil starting with water-colour drawings of João Barbosa Rodrigues, a Brazilian naturalist of the XIX Century, in his album Iconographie des Orchidées du Brésil. Considering the fact that he was a pioneer in the introduction to botanical illustration as an essential element in botanical research in Brazil, this work aims at the nature of the visuality of his work through its historical, social and formal involvement. For this, there will be covered within: the origin of botanical illustration as a discipline to record the search for human knowledge from the beginning of time; the nature of Portuguese Illuminist reform of the Marquês de Pombal, in that which refers to research of the natural resources of Brazil; the significance of botanical expeditions in Brazil and the participation of Brazilian naturalists in them; João Barbosa Rodrigues's efforts towards introduction and development of Brazilian science and botanical illustration and the difficulties which led to the work in question not being published until 1996.